The Challenges of Psychology at Work in Mental Health: the drugs issue. - Castro, Edson Olivari de [UNESP] (My University, 2013)
This article aims to show that the challenges of psychology in working with mental health in the field of drugs is traversed by both the conceptions molded by biopolitical forces (FOUCAULT) as the decadence of modern democracy (AGAMBEN), and visible features in the current treatment given in Brazil to issue of smoking (SILVA), as well as urbanistic projects such as the case of Luz district in São Paulo (LEITE & CASTRO). In this sense, it leads us to question about what is prohibited, about who actually suffers the punishment, in short, about what do we really take care when we take into account the Unheimlich (FREUD) and other social interdicts (BATAILLE).
Keywords: Mental health; Public politics on drugs; Biopolitics; Psychology and Psychoanalysis